DEVELOPMENT OF THE SYSTEM OF OF-LINE OF THE INTERMEDIATE (MODULAR) TESTING WITH FOTO-VIDEO FIXING WHICH STIMULATES THE STUDENT TO EXECUTION OF REQUIREMENTS AND RULES OF CARRYING OUT CONTROL ACTIONS - Mazur М.П.; Yanovsky М.Л. (Journal of Information Technologies in Education (ITE), 2015)
The majority of the existing testing systems provide access to test jobs by means of various software: password entry from the keypad, a voice in a microphone, scanning of fingerprints, the signature of the student or other devices. Thus the subsequent course of testing, as a rule, isn’t traced that can be a basis for abuses. The system developed in Khmelnytsky national university ofline of testing with photo video fixing is integrated with the parameter assigned to each student – «a trust rating». Change of this parameter, changes testing procedure for the student: from self-test from any point of the world, to passing of this procedure on the remote information and communication center of university and up to testing under monitoring of the teacher at the central university. As a result of it the teacher-tutor receives the protocol of testing which contains the photos of all procedure of monitoring and results of responses of the student to each question taken through an accidental interval of time. Results of the protocol the teacher are claimed or void.Results of photo video fixing and responses to test jobs allow the teacher to receive information for the analysis of educational process of the student, an assessment of quality of tests, and opportunity with their help to evaluate the level of knowledge of the student.